Innovators or Risk-Avoiders? The Role of Female Executives in Enterprise Innovation in China - Tingqian Pu (Review of Business and Economics Studies)
The author examines the relationship between female executives and enterprise innovation in Chinese A-share listed companies. The subject of the study is the impact of female executive representation on research and development (R&D) investment and innovation output in firms. The purpose of the research is to determine whether female executives inhibit innovation performance and to explore the mediating role of R&D investment while also assessing the variation of effects between state-owned and non-state-owned enterprises. The relevance lies in the growing international interest in understanding how gender diversity in top management affects firm-level strategic outcomes, especially in emerging markets with distinct institutional and cultural contexts. The scientific novelty lies in the empirical identification of the mechanism through which female executives affect innovation, using a panel dataset of 3,920 Chinese listed companies over the period 2012 to 2021. As part of the study, the author used the methods of two-way fixed effects, mediation analysis to assess indirect effects through R&D investment, and heterogeneity analysis to compare state- versus non-state-owned enterprises. Based on the results, it was found that female executives are significantly associated with reduced innovation output, primarily due to lower R&D investment. The author concluded that gender-based differences in risk-taking behavior influence innovation outcomes and that these effects may also be shaped by institutional settings and ownership structures.